Validation of Decisional Procrastination Instrument - Ling, Kelvin; Yuwanto, Listyo; Siaputra, Ide Bagus (ANIMA Indonesian Psychological Journal, 2012)
There are various types of procrastination, one of which is decisional procrastination (Ferrari, Johnson, & Mann, 1995). This study aimed to translate and test the validity of the Decisional Procrastination (DP) instrument in Indonesian language. The subjects in this study were 112 active psychology students of the 2010 generation. Data was collected by distributing DP instrumentsin two languages to each subject. Based on the two criterias of validity test proposed by AERA, APA, and NCME (1999), the translated DP instrument version (in Indonesian language) proved to meet the requirement as a valid and reliable psychological measure. Prokrastinasi terdiri atas beberapa jenis, salah satunya adalah decisional procrastination (Ferrari, Johnson, & Mann, 1995). Penelitian ini bertujuan untuk mengalihbahasakan dan menguji validasi alat ukur DP ke dalam bahasa Indonesia. Subjek yang digunakan dalam penelitian ini adalah 112 mahasiswa fakultas psikologi angkatan 2010. Pengambilan data dilakukan dengan membagikan skala DP dalam dua bahasa sekaligus kepada masing-masing subjek. Berdasarkan dua kriteria uji validitas yang diusulkan oleh AERA, APA, dan NCME (1999) diketahui bahwa DP dalam versi terjemahan (bahasa Indonesia) terbukti memenuhi kaidah sebagai alat ukur psikologis yang valid dan reliabel.